Intermediate clinical endpoints for surrogacy in localised prostate cancer: an aggregate meta-analysis. Issue 3 (March 2021) - Gharzai, Laila A; Jiang, Ralph; Wallington, David; Jones, Gavin; Birer, Samuel; Jairath, Neil; Jaworski, Elizabeth M; McFarlane, Matthew R; Mahal, Brandon A; Nguyen, Paul L; Sandler, Howard; Morgan, Todd M; et al.
Summary: Background: The international Intermediate Clinical Endpoints in Cancer of the Prostate working group has established metastasis-free survival as a surrogate for overall survival in localised prostate cancer based on the findings of 19 predominantly radiotherapy-based trials. We sought to comprehensively assess aggregate trial-level performance of commonly reported intermediate clinical endpoints across all randomised trials in localised prostate cancer. Methods: For this meta-analysis, we searched PubMed for all trials in localised or biochemically recurrent prostate cancer published between Jan 1, 1970, and Jan 15, 2020. Eligible trials had to be randomised, therapeutic, reporting overall survival and at least one intermediate clinical endpoint, and with a sample size of at least 70 participants. Trials of metastatic disease were excluded. Intermediate clinical endpoints included biochemical failure, local failure, distant metastases, biochemical failure-free survival, progression-free survival, and metastasis-free survival. Candidacy for surrogacy was assessed using the second condition of the meta-analytical approach (ie, correlation of the treatment effect of the intermediate clinical endpoint and overall survival), using R 2 weighted by the inverse variance of the log intermediate clinical endpoint hazard ratio. The intermediate clinical endpoint was deemed to be a surrogate for overall survival if R 2 was 0·7 or greater. Findings: 75 trials (53 631 patients) were included in our analysis. Median follow-up was 9·1 years (IQR 5·7–10·6). Biochemical failure ( R 2 0·38 [95% CI 0·11–0·64]), biochemical failure-free survival ( R 2 0·12 [0·0030–0·33]), biochemical failure and clinical failure ( R 2 0·28 [0·0045–0·65]), and local failure ( R 2 0·085 [0·00–0·37]) correlated poorly with overall survival. Progression-free survival ( R 2 0·46 [95% CI 0·22–0·67]) showed moderate correlation with overall survival, and metastasis-free survival ( R 2 0·78 [0·59–0·89]) correlated strongly. Interpretation: Intermediate clinical endpoints based on biochemical and local failure did not meet the second condition of the meta-analytical approach and are not surrogate endpoints for overall survival in localised prostate cancer. Our findings validate metastasis-free survival as the only identified surrogate endpoint for overall survival to date. Funding: Prostate Cancer Foundation and National Institutes of Health.